The Proposal of a Conceptual Model of Brand Equity in the New Logic of Services - D'Avila Gonçalves, Livia Castro; Garrido, Ivan Lapuente; Damacena, Cláudio (Review of Business Management, 2010)
The study about brand value and brand equity is considered one of the main topics in the strategic management of marketing (Webster, 2005). Much emphasis has been given to studies about this subject in relation to services, for presenting characteristics which distinguish them from products (Berry, 2000). Besides that, Vargo and Lusch (2004a) propose a new way of studying services, inspired by the transfer of a logic where tangible goods are the central topic, to a logic in which the intangible aspects and the interaction with the consumer are central (Service-Dominant Logic). In this proposal, brand is a topic forgotten by the authors, in spite of its recognized relevance (Brode, Glynn, Little, 2006). The objective of this article is to propose a conceptual model of brand value antecedents in services under this new approach. Following an exploratory approach a theoretical review is presented about brand equity and the elements of this new dominant logic. A set of antecedents of brand equity is proposed in this context, based on the model of Berry (2000), considering to keep the elements already identified by the author (brand presented by the company, external communication and consumers experience with a company), and indicating the inclusion of the elements Brand Personality and Co-creation. As the result, the study offers a model that can be the base for a new perspective in management and research in services brand equity. Key words: Brand equity. Services. New logic.